Structural performance of Ti6Al4V tibial tray in Total Knee Arthroplasty (TKA) by functionally graded lattice structures using numerical analysis / Nurasyrani Rabuan ... [et al.] - Rabuan, Nurasyrani; Adenan, Mohd Shahriman; HP Manurung, Yupiter; Mohd Anuar, Mohd Afzan; Shuib, Solehuddin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
The medical industry benefits greatly from the additive manufacturing (AM) technology used on customized products. Total knee arthroplasty (TKA) has been widely used however it has drawbacks of stress shielding and loosening due to the excessive daily routine of patients. The problem could be minimized by applying lattice structures to the implant and mimicking the actual density of human bone. This study aims to investigate the optimal design of a Ti6Al4V alloy tibial tray by applying different types of lattice structure designs. A finite element analysis was used to investigate the mechanical behavior of uniform and non-uniform lattice structures in a walking position. Functional gradation structure was optimized on selected regions of the tibial tray with weight reduction and adaptation to the near actual density of the human bone without compromising its mechanical performance. The results indicated that the Voronoi structure has improved stress behavior and the capability to withstand the loads exerted, based on the Von Mises stress result of the Voronoi structure at 35.83 MPa as compared to the gyroid and diamond structures at 61.65 MPa and 49.74 MPa, respectively. The optimal design of the tibial implant was achieved by functionally graded lattice structures, replacing the solid tibial implant.